Finite-set MPC-based Power Synchronization Control for Grid-Forming Inverters - Cai, Yuxi; Hou, Chuanchuan; Zhu, Miao; Gong, Xundong; Yang, Chen (IEEE Conference on Industrial Electronics and Applications (Online), 2025)
A power synchronization control (PSC) system for grid-forming inverters based on Model Predictive Control (MPC) is proposed in this paper to enhance phase tracking accuracy under complex grid conditions. Unlike conventional PI-based PSC systems, the proposed MPC-PSC can adapt to abnormal grid conditions without relying on fixed parameters. A finite control set for phase adjustment is introduced, and real-time optimization is employed to determine the optimal phase increment. Furthermore, this paper addresses the research gap where MPC has not been applied to the phase synchronization mechanism of grid-forming inverters. Simulation results demonstrate that accurate synchronization and fast recovery during sudden grid voltage changes can be achieved by the proposed MPC-PSC, with excellent transient performance.